Characteristics of N-acetyltransferase 2 Phenotype Status and Pharmacokinetic Parameters of Vietnam Pulmonary Tuberculosis Patients - Anh Tuan, Le; Son Nhat, Bui; Thi Luyen, Le; Minh, Vu Duong Anh; Ba Hai, Le; Thi Thu Trang, Tran; Thi Lien Huong, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3, 2022)
Abstract: We conducted this research to determine the NAT2 gene-phenotype characteristics and pharmacokinetics (PK) parameters of isoniazid among patients with non-MDR pulmonary tuberculosis. Data were collected from 132 patients diagnosed with newly acquired or relapsed tuberculosis and treated at 03 hospitals: Hanoi Lung Hospital, Central Lung Hospital, and National K74 Hospital. PK samples were collected one day from the 10 th – 14 th day after commencing treatment. The average age of the recruited patients was 45.43 ± 15.76 years; the majority were male (74.24%). The slow and medium acetylator types, as indicated by NAT2 phenotypes, were the two major types (37.88% and 35.6%, respectively). 61.12% of the patients had their Bayesian isoniazid-acetyl isoniazid population PK modeling - determined Cmax value within the therapeutic range of 3 – 6 µg/mL. Acelytator type showed a statistically significant correlation with Cmax. Keywords : Isoniazid, pharmacokinetics, Cmax, tuberculosis.